1993
DOI: 10.3109/02813439308994909
|View full text |Cite
|
Sign up to set email alerts
|

Ketoprofen controlled release (CR) in the treatment of osteoarthrosis; a double blind, randomized multicentre study of single morning versus evening dose

Abstract: Ketoprofen controlled release given once daily in the morning compared to the evening to patients with osteoarthrosis may increase the efficacy without reducing the tolerability of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Analysis of two clinical studies with ketoprofen [49,50] revealed equivocal information precluding a clear recommendation. Taking the reported indication and pharmaceutical form reported in the literature into account, the percentage of drug administrations in concordance with the suggested time of administration for individual drugs were 0% for telmisartan (bedtime), 0.2% for aspirin and ramipril (bedtime), 1% for theophylline (evening), 16% for quinapril (evening), 51% for amlodipine (morning), 62% for simvastatin (evening), 83% for atorvastatin (evening), and 85% for perindopril (morning).…”
Section: Analysis Of Clinical Trialsmentioning
confidence: 91%
“…Analysis of two clinical studies with ketoprofen [49,50] revealed equivocal information precluding a clear recommendation. Taking the reported indication and pharmaceutical form reported in the literature into account, the percentage of drug administrations in concordance with the suggested time of administration for individual drugs were 0% for telmisartan (bedtime), 0.2% for aspirin and ramipril (bedtime), 1% for theophylline (evening), 16% for quinapril (evening), 51% for amlodipine (morning), 62% for simvastatin (evening), 83% for atorvastatin (evening), and 85% for perindopril (morning).…”
Section: Analysis Of Clinical Trialsmentioning
confidence: 91%
“…Morning dosing of ketoprofen controlled release (200 mg) increased the efficacy without reducing the tolerability in patients with osteoarthrosis when compared with evening dosing. The reduction in the degree of pain in the afternoon and in the evening was significantly higher for the morning dose (66). However, total and GI side effects were twofold greater in patients taking ketoprofen in the morning than at night, as described in a double‐blind trial with 118 osteoarthritis outpatients receiving a 200 mg ketoprofen slow‐release tablet (67).…”
Section: Drugs Acting On Metabolism and Endocrine Systemmentioning
confidence: 99%
“…The analgesic effect was increased by about 60% when the NSAID was taken at the preferred time (about 6 h prior to the usual time of day of worse osteoarthritic pain) compared with when it was ingested at the non‐preferred times of the day (64,65). With regard to the safety profile, a double‐blind, cross‐over trial of a 3‐week duration involving 66 patients concluded that adverse effects were consistently greater in occurrence and in severity when indomethacin sustained release was ingested at 8 am than at any other time of the day (66). Morning dosing of ketoprofen controlled release (200 mg) increased the efficacy without reducing the tolerability in patients with osteoarthrosis when compared with evening dosing.…”
Section: Drugs Acting On Metabolism and Endocrine Systemmentioning
confidence: 99%